1998
DOI: 10.1021/jo972180+
|View full text |Cite
|
Sign up to set email alerts
|

C−O and C−S Bonds:  Stability, Bond Dissociation Energies, and Resonance Stabilization

Abstract: The structures and energies of the compounds XC(O)OH, XC(S)OH, XC(O)SH, and XC(S)SH, where X = CH3, NH2, OH, and F, were obtained at the MP2/6-31+G(2d) theoretical level, and energies were calculated at the MP3/6-311++G(2d,p), CBS-4, and G2 theoretical levels. These data show that XC(O)SH is preferred over XC(S)OH by 5 kcal/mol with X = CH3, and the preference increases to 12 kcal/mol with X = F. The C−O(H) bond dissociation energies were greater than the C−S(H) energies by approximately 30 kcal/mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 37 publications
3
50
0
Order By: Relevance
“…On the other hand, although a theoretical study suggests that a CϭO bond is more stable than a CϭS bond in general, [10] it is not clear why, in the BF 3 ·OEt 2 -catalyzed reaction of methyl phenyldiazoacetate, the CϭS bond in the initially formed product 5 can be easily replaced by CϭO, while the CϭS bond is relatively stable in 7a, 7b and 7c. In the case of 5, we speculate that enolization occurs readily because of the stabilizing effect of the phenyl ring.…”
Section: Resultsmentioning
confidence: 94%
“…On the other hand, although a theoretical study suggests that a CϭO bond is more stable than a CϭS bond in general, [10] it is not clear why, in the BF 3 ·OEt 2 -catalyzed reaction of methyl phenyldiazoacetate, the CϭS bond in the initially formed product 5 can be easily replaced by CϭO, while the CϭS bond is relatively stable in 7a, 7b and 7c. In the case of 5, we speculate that enolization occurs readily because of the stabilizing effect of the phenyl ring.…”
Section: Resultsmentioning
confidence: 94%
“…There are precedents for S-alkylation of secondary thiobenzamides under basic conditions with alkyl iodides, [43,44] a sulfenyl chloride [45] and a phosphinoyl chloride. [46] For the reaction with acyl halides, both regioselectivities Ϫ acylation of the sulfur atom [47] or of the nitrogen atom [48,49] Ϫ have been reported. Our results are clear-cut.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, another ab initio study 44 has demonstrated that the C O bonds are stronger than the CS bonds, which can help to explain why some of the thiocarbonyl substitutions are unstable, but it would not explain why others are stable. It would seem that in the present cases, the unstable molecules are also those that have a nonplanar conformation.…”
Section: ■ Introductionmentioning
confidence: 97%